Development of Small Games for Motoric Skills of Primary School Students in Rambang Kapak Tengah Subdistrict - Utama, Sari Fitri; Manullang, Jujur Gunawan; Putri, Siti Ayu Risma (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
The need for small games is still a severe concern for PJOK SD teachers in the Rambang Kapak Tengah subdistrict, considering that the problems faced by students in the current technological era impact the poor quality of students’ motor skills. Small games play a crucial role in physical education as they allow students to develop various skills in a fun and engaging way. These games help improve physical fitness and promote teamwork, communication, and strategic thinking. By incorporating small games into physical education classes, teachers can create a dynamic learning environment that motivates students to participate actively and develop a lifelong love for physical activity. This research aims to determine the development of small games for valid and practical motor skills for Prabumulih City elementary school students. This research is an RnD research with an ADDIE research design. Field trials were conducted on students at SDN 62 in the Rambang Kapak Tengah subdistrict. Data collection was carried out by distributing questionnaires. Data analysis was carried out based on percentage analysis. This research produced ten types of small games for students’ motor skills. These games include the Jaripapat game, the popular game, the Ringkup game, the Lakar game, the lontang game, the Keder game, the Umkap game, the Lekar game, the Lorung game and the Lodeng game.